Perbandingan Ekstrak Etanol Daun Tanaman Matoa (Pometia Pinnata) Dan Daun Rambutan (Nephelium Lappaceum) Terhadap Kadar Kolesterol Tikus yang Diberikan Induksi Pakantinggi Kolesterol - Saogo, Shintia Astika (Jurnal Medisains Kesehatan, 2025)
Hypercholesterolemia is a significant global health problem, increasing the risk of cardiovascular diseases such as coronary heart disease and stroke. This study aims to compare the effectiveness of ethanol extracts of the two leaves in lowering cholesterol levels in mice induced by high-cholesterol feed. This study used an experimental design with a post-test only control design. A total of 24 male mice (Mus musculus) aged 8 weeks with an average weight of 20 grams were used as experimental animals, then divided into 3 groups: control (standard feed), treatment 1 (induced with high-cholesterol feed, then given Matoa leaf extract 300 mg/kgBW), and treatment 2 (induced with high-cholesterol feed, then given Rambutan leaf extract 70 mg/kgBW). High-cholesterol feed induction was carried out for 7 days using 3 ml of lard and 3 quail egg yolks. Cholesterol levels were measured using an autocheck tool. The measurement data were analyzed using SPSS with a one-way ANOVA test. The data normality test showed a normal distribution, and the one-way ANOVA test showed a significant difference between treatment groups (p<0.05). This decrease was caused by the flavonoid content in both extracts which inhibited cholesterol absorption in the intestine and increased bile acid excretion. Based on these results, it can be concluded that rambutan leaf extract at a dose of 70 mg/kgBW is more effective because of its antioxidant and fiber content which helps bind. This study provides a scientific basis for the potential use of these two plants as herbal medicines to lower cholesterol.